Synonymy of Hooperella spinirostra (Vercammen-Grandjean, 1967) with Hooperella vesperuginis (Brennan and Jones, 1960): redescription based on the types, new locality and host records from Brazil - Bassini-Silva, Ricardo [UNESP] (2023)
The New World genus Hooperella Vercammen-Grandjean has five valid species that are often collected parasitizing bats. Two of these species were examined in the present study, Hooperella spinirostra and Hooperella vesperuginis. Moreover, after examining both types, we propose H. spinirostra as a junior synonym of H. vesperuginis, since no difference was observed between them. In addition, we add new locality and host records for H. vesperuginis.